A Reflected Forward-Backward Splitting Method for Monotone Inclusions Involving Lipschitzian Operators - Cevher, Volkan; Vũ, Bằng Công (Set-valued and variational analysis, 2021)
In this paper, we propose a novel splitting method for finding a zero point of the sum of two monotone operators where one of them is Lipschizian. The weak convergence the method is proved in real Hilbert spaces. Applying the proposed method to composite monotone inclusions involving parallel sums yields a new primal-dual splitting which is different from the existing methods. Connections to existing works are clearly stated. We also provide an application of the proposed method to the image denoising by the total variation.